(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The paper sets out to evaluate and appraise the roles of mass media and press freedom in the process of democratic consolidation in Nigeria’s Fourth Republic (1999-2019); and the nexus between mass media, press freedom and democracy. In addition, the paper discusses the conceptual meaning of mass media, press freedom, democracy and democratic consolidation. The paper also identifies the factors acting as constraints to the effectiveness of the print and electronic media in ensuring democratic consolidation. The data for this study were collected through secondary sources. The secondary data were retrieved from textbooks, journals, newspapers, internet materials and literatures from academic journals in relation to the subject studied. The study adopted social responsibility theory of the press and Agenda Setting theory as a theoretical framework. Findings revealed the need for the autonomy of the mass media as a needed instrument for the stability of the democratic process. The paper observes that the sustainability of democracy in Nigeria depends on several factors, some of which are located within the media itself while others are based on the prevailing political, socio-economic, legal, infrastructural, cultural and religious environment of the country. The paper concludes that the role of mass media and press freedom is facilitative, supportive and integrative to Nigeria democratic consolidation. To achieve greater media effectiveness in promoting democratic ideals and governance in Nigeria, there is need for private sector partnership and involvement of civil society organizations in media ownership in order to achieve a balance.